Consultoria colaborativa: influências na autoeficácia docente e no processo de inclusão de alunos com transtorno do espectro autista - Canabarro, Renata Corcini Carvalho (2018)
According to the Social Cognitive Theory, the sense of teacher self-efficacy does not refer to the abilities one possesses, but to the judgment of feeling capable of developing pedagogical action effectively. Thus, the perception of trust regarding professional practice can interfere in the schooling of students with Autism Spectrum Disorder (ASD) and affect the motivation and role of the teacher when facing challenging situations of the inclusion of these students. In this perspective, the present study proposed to evaluate the influences of the process of collaborative consultation on the sense of teacher self-efficacy of a special education teacher who works with students with ASD. This central objective was divided into other more specific ones: to carry out the translation and cross-cultural adaptation of the Autism Self-Efficacy Scale for Teachers (ASSET) to Brazilian Portuguese; to develop the collaborative consultation process in the ASD area along with the special education teacher; and to verify the quality of the inclusion process of students with ASD and its relation with the actions of the special education teacher resulting from collaborative consulting. In addition to the objectives, the following specific objectives were also considered: verifying indicators of teachers' sense of self-efficacy of the special education teacher in relation to the insertion of collaborative consulting; and to analyze the influence of emotional and behavioral factors of the special education teacher and students with ASD on the sense of teacher self-efficacy related to the development of collaborative consulting. The research design consisted of a single integrated case study since it involved a single case (special education teacher), although it focused on an analysis subunit (students with ASD). The collaborative consultation was developed in a Primary School of the Rede Municipal de Ensino of Santa Maria-RS using 15 face-to-face meetings with the special education teacher responsible for the Special Education Service of two students with ASD. The influences of collaborative consultation on teacher self-efficacy were identified by ASSET, translated, and adapted to Brazilian culture before (pre-test) and after (post-test), as well as, through other measures of the participant and students with ASD. Data were submitted to quanti-qualitative analysis. Results showed an increase in teacher self-efficacy perceived by the special education teacher and revealed some significant relationships between the teaching actions and inclusion process of students with ASD. Peculiarities of collaborative consultation and the planned and incidental situations resulting from this process may have favored the expansion of information about the sources of self-efficacy development (direct experience, vicarious experience, social persuasion, and physical/emotional states) favoring positive influence on strengthening self-efficacy. Despite variations in the scores of some point items on the scale, elevation of the perception of self-efficacy was maintained even after the collaborative consultation was completed, as the follow-up data indicated, with a 5-month interval.